A political theology in 16th century Peru - Gutiérrez, Gustavo (1982)
The so-called "anonymous person from Yucay" is an important witness to the theological-juridical discussions motivated by the conquest of the Indies. The title of the manuscript found in the National Library of Madrid indicates precisely its subject: "Opinion on the domain of the Yngas and Kings of Spain in the Kingdoms of Peru." It is specifically a relationship made to support the right of the kings of Spain over the kingdom of Peru, the last to have been conquered in the Indies. The anonymous author writes from Yucay, a place near Cusco, in the very heart of the Inca empire.